S64 Understanding better the pathophysiology of aspiration pneumonia. (2nd December 2011) - Vaishnavi, A; Satia, I; Balasubramanian, D; Sundar, R
Abstract : Background: Aspiration of oropharyngeal or gastric contents into the lower airways can cause a number of syndromes including chemical and bacterial pneumonia, although the pathophysiology of each entity is different.1 Data from Dr Foster's Guide and our local coding department revealed a high incidence and mortality from aspiration pneumonia alerting us to study those patients. Methods: Retrospective analysis of 53 patients coded as aspiration pneumonia from February 2010 to March 2011. Analysis of presentation, investigations, management, pre-disposing factors and outcome was undertaken. Results: Average Age 78, M/F ratio (1:1). Out of 53 coded as aspiration pneumonia, 2 were re-coded to an alternative diagnosis. Out of 51 patients, 36 died (71%) and 15 survived but 17/51 (23%) had chest x-rays which were not suggestive of aspiration pneumonia. Of the 36 patients that died, 67% showed positive x-ray changes, while the 15 survivors had 80% x-rays suggesting pneumonia. Abstract S64 table 1 shows the list of clinical presentations and potential risk factors. On average each patient had 4 out of the 7 clinical features positive. 23/51 (45%) had either a basic swallow or SALT assessment of whom only 2/23 (9%) passed. 0/51 (0%) proceeded to mechanical ventilation. 51/51 (100%) had oxygen, intravenous fluids and antibiotics. Conclusion: Aspiration pneumonia has a high mortality, particular in those with a history of aspiration living in residential or nursing facilities. 23% of patients with a good clinical history of aspiration did not show x-ray changes to suggest pneumonia. It may suggest a difference in the pathophysiology of lung injury in these patients who aspirate acidic gastric contents causing a chemical injury without x-ray changes of pneumonia. Although the treatment at present is no different, research needs to be incorporated into guidelines to diagnose, prevent and treat the different types of aspiration.